The Human Potential and its Role in Business Development - Raluca-Ana-Maria, Dumitru (Annals of Spiru Haret University. Economic Series, 2017)
Through its object of activity, an economic organization has the role to use efficiently the means of production that it possesses in terms of the full utilization of the production capacities, of a high quality of the products and of obtaining profit. Companies need in their human, material, financial, informational, human resources activities that they have at a certain moment in order to accomplish the mission and strategic objectives around which they rely on the whole activity.